Manufacturing process of highly wear-resistant and scratch-resistant diamond sand-feeling pattern
By using a high-wear-resistant and scratch-resistant diamond-textured pattern manufacturing process, the problem of easy scratching and ink fading of packaging boxes during transportation and use has been solved. This process achieves wear-resistant, scratch-resistant, and unique visual and tactile effects, enhancing the durability and premium feel of the packaging boxes while ensuring registration accuracy.
Patent Information
- Application Number
- CN202511592933.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-03
- Publication Date
- 2026-01-23
AI Technical Summary
Dark-colored printed materials on existing packaging boxes are prone to scratches and ink fading during transportation and use, and existing processes are difficult to improve wear resistance and registration accuracy while maintaining a high-end texture.
Employing a highly wear-resistant and scratch-resistant diamond-textured pattern manufacturing process, the design utilizes UV printing, holographic lithography, and PET film lamination, combined with special sand-textured oil and platinum positioning paper lithography effects to achieve lens and laser effects. By controlling ink density and coating parameters, a wear-resistant, scratch-resistant, and unique visual and tactile effect is achieved.
It improves the wear resistance and scratch resistance of the packaging box, enhances the visual and tactile effects, reduces friction damage during transportation, maintains the integrity of the product's appearance and its premium feel, and at the same time improves the registration accuracy and recognizability.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the packaging field, and in particular to a high-wear-resistant anti-scratch diamond sand pattern manufacturing process. BACKGROUND
[0002] In the packaging field of consumer electronics, the packaging box not only bears the basic function of protecting the product, but also becomes an important carrier for conveying brand value, improving product grade and attracting consumers. With the increasing demand of consumers for product appearance texture, technological sense and fashion sense, dark color packaging is widely used in high-end electronic products such as smart phones and smart wearable devices due to its stable and high-end visual effect. However, the dark color printing product is prone to surface scratches, ink loss and other problems during transportation, storage and use, which seriously affects the appearance and user experience of the product.
[0003] At present, the industry often uses reverse UV sanding process to achieve special touch and visual effect on the surface of the packaging. This process forms a delicate sanding texture by locally coating reverse UV ink on the printed text after curing, which has strong decorative effect. However, practice shows that this process has significant defects: first, when performing secondary processing such as gold stamping on the surface that has been treated with reverse UV sanding, the adhesion between the gold stamping layer and the sanding surface is poor, and jagged marks or scratches are easily generated at the edge; second, when printing black ink on a large area of positioning silver card paper and combining with the reverse UV sanding process, the finished product generally has friction discoloration after vibration transportation test, which is difficult to meet the strict requirements of the consumer electronics industry on packaging durability.
[0004] To solve the above wear resistance problem, some enterprises try to use film coating process to protect the surface of the printed product. Although the film coating can effectively improve the surface scratch resistance, it weakens the high-grade texture of the packaging.
[0005] In addition, the realization of complex optical effects such as lens magnification and laser halo in the prior art depends on independent gold stamping or holographic transfer paper process, which is complicated and difficult to control the registration accuracy, and is prone to problems such as pattern misalignment and edge burr, especially at the edge of fine text or numbers, which affects the overall appearance and brand tone.
[0006] The present application is made based on the above situation. SUMMARY
[0007] The present application overcomes the shortcomings of the prior art and provides a high-wear-resistant anti-scratch diamond sand pattern manufacturing process, which is a packaging surface treatment process that integrates high wear resistance, scratch resistance, unique visual and tactile effects, and solves the problems of registration accuracy and adhesion in multi-process joint operation.
[0008] The present application is realized by the following technical solutions:
[0009] A high-wear-resistant anti-scratch diamond sand pattern making process, comprising the following steps:
[0010] S1, graphic pre-design, according to the required design effect picture, the effect picture has three parts of main pattern, halo and bright light;
[0011] S2.1, printing ink is printed on platinum positioning paper by UV printing machine to form effect picture;
[0012] S2.2, using holographic lithography technology, the halo and bright light part of the effect picture which needs to be decorated is molded, so as to produce lens and laser effects on the same page;
[0013] S2.3, the halo part is controlled by printing two groups of special black ink with different color depth to control the intensity of lens light effect, and the main pattern part is imaged by laser technology;
[0014] S3.1, PET light film is pasted, and the product is pasted within 8-12 hours after printing;
[0015] S3.2, the product pasted with PET light film is put into a constant temperature and humidity workshop for storage for 8-12 hours for processing;
[0016] S4, the front of the product pasted with PET light film is coated with varnish, and the surface of the product after processing reaches a diene value of 38 or more;
[0017] S5, the product coated with varnish is printed with sand oil by UV printing machine, the bottom oil of the sand oil is special sand oil, and the surface oil of the sand oil is special sand coating diamond oil;
[0018] S6, the product is knocked out, die cut and formed into a box.
[0019] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, in step S2.1, the color sequence of printing is special black, C, M and Y, the density of special black ink, C ink, M ink and Y ink is 1.2-1.8g / cm 3 .
[0020] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, the density of the special black ink is 1.6-1.8g / cm 3 , the density of the C ink is 1.5g / cm 3 , the density of the M ink is 1.4g / cm 3 , and the density of the Y ink is 1.2g / cm 3 .
[0021] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, in step S5, the model of the special sand oil is UV HU 1221, and the model of the special sand coating oil is UV HU 1220.
[0022] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, the ink amount of the base oil is 1.5 g / m 2 , and the ink amount of the surface oil is 5 g / m 2 .
[0023] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, after step S2.3 and before step S3.1, the adhesion of the ink is tested by 3M tape.
[0024] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, in step S3.1, the pressure of the film laminating is controlled at 160-165 kgf, the speed is 20-25 m / min, and the temperature is 95-100 DEG C. The dyne value of the laminated glue is tested by a dyne pen, and the value needs to reach 36 or more.
[0025] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, in step S4, the model of the varnish is water-based HH-818.
[0026] The high-wear-resistant anti-scratch diamond sand pattern making process as described above, after step S5 and before step S6, the adhesion of the sand oil is tested by 3M tape, the GB wear-resistant test is greater than 1000 times, and the sand oil does not fall off after being folded back 90 DEG three times.
[0027] Compared with the prior art, the present application has the following advantages:
[0028] The present process applies special sand oil on the surface of the package, so that the finished product not only has strong visual impact, but also is more wear-resistant and scratch-resistant than the anti-scratch matte film on the market. This feature can effectively resist friction damage during transportation and maintain the integrity of the product appearance. Some traditional processes have poor adhesion between the gold stamping layer and the matte surface when gold stamping and other secondary processing are performed on the reverse UV matte surface. The laser effect pattern in the present process is under the film and is not easy to fall off. The special sand oil is printed on the film and is not easy to scratch. There is no plastic sealing film outside the special sand oil, and the product has a high-grade feel.
[0029] The holographic lithography technology is used to produce lens and laser effects on the same page, and the depth of two groups of special color black ink is adjusted to control the intensity of the lens light effect and create a unique and delicate halo effect. This not only enhances the fashion and technology of the package, but also enhances the recognition and attractiveness of the product.
[0030] The main pattern is achieved by using the photoetching effect of the platinum positioning paper to achieve the effect that can only be achieved by hot stamping laser silver, thereby reducing the risk of main pattern abrasion and jagged edges in the printing production process. DETAILED DESCRIPTION
[0031] The application is further described below:
[0032] The application discloses a high-wear-resistance anti-scratch diamond sand feeling pattern manufacturing process, comprising the following steps:
[0033] S1, graphic pre-design, design an effect graphic according to the requirement, the effect graphic has three parts of a main pattern, a halo and a bright light;
[0034] S2.1, printing ink is printed on the platinum positioning paper by a UV printing machine to form the effect graphic;
[0035] S2.2, the halo and the bright light parts that need to be decorated on the effect graphic are molded by using holographic photoetching technology, so that lens and laser effects are generated on the same page;
[0036] S2.3, the intensity of the lens light effect is controlled by printing two groups of special black inks with different color depths on the halo part, and the main pattern part is imaged by the photoetching laser technology;
[0037] The pattern tolerance error of the platinum positioning paper is less than or equal to 1 mm, and a visual positioning instrument is used to monitor the stability of the quality.
[0038] S2.4, the adhesion of the ink is tested by 3M600 adhesive tape.
[0039] S3.1, PET light film lamination, after printing, the product is laminated within 8-12 hours; there is a risk of inaccurate overlaying if the time exceeds this period.
[0040] S3.2, the product laminated with the PET light film is placed in a constant temperature and humidity workshop for storage for 8-12 hours for processing;
[0041] S4, the front of the product laminated with the PET light film is coated with varnish, and the diene value of the surface after processing is greater than 38;
[0042] S5, the product coated with varnish is printed with sand feeling oil by a UV printing machine, the base oil of the sand feeling oil is special sand feeling ink hopper diamond oil, and the surface oil of the sand feeling oil is special sand feeling coating diamond oil;
[0043] S5.1, the adhesion of the sand feeling oil is tested by 3M600 adhesive tape, the GB wear resistance test is greater than 1000 times, and the sand feeling oil does not fall off after being folded back 90° three times.
[0044] S6, the product is subjected to knockout, die cutting and box sticking forming.
[0045] The process uses special sand oil to improve the wear-resistant and scratch-resistant performance of the packaging, effectively resisting transportation friction; through the holographic lithography technology combined with different special color black ink, the lens and laser double light effects are realized on the same page, presenting delicate halo, enhancing visual attraction and product recognition; at the same time, the lithography effect of platinum positioning paper is used to replace the traditional laser silver process, reducing the risk of main pattern wear and sawtooth, improving the printing quality.
[0046] In some embodiments, in step S2.1, the color sequence of printing is special black, C, M, Y, and the density of special black ink, C ink, M ink, and Y ink is 1.2-1.8 g / cm 3 .
[0047] Further, the density of the special black ink is 1.6-1.8 g / cm 3 , the density of the C ink is 1.5 g / cm 3 , the density of the M ink is 1.4 g / cm 3 , and the density of the Y ink is 1.2 g / cm 3 .
[0048] The color sequence of printing is special black first, and the density is controlled in a higher range of 1.6-1.8 g / cm 3 , which can realize high saturation and complete coverage of the dark color layer, effectively avoid the visual dullness or mottling phenomenon caused by the bottom color transmission, and improve the overall visual quality. Reasonable color sequence arrangement (special black→C→M→Y) avoids the interference of high-absorption ink on the previous color when printing, reduces the color mixing or sticking problem caused by reverse overprinting. At the same time, the step-by-step decreasing ink density design helps to control the ink accumulation amount, prevent paper deformation or drying failure caused by excessive ink absorption, and ensure multi-color overprinting accuracy. Scientific matching of ink density and optimization of printing order help to form a dense and fully dried ink layer, providing a good adhesion basis for subsequent film mounting, varnish coating and sand oil printing, reducing defects such as delamination and blistering caused by incomplete drying or uneven surface energy of the ink layer.
[0049] In some embodiments, in step S5, the model of the special-effect sand-touching printing ink for the bottom oil is UV HU 1221, and the model of the special-effect sand-touching printing ink for the surface oil is UV HU 1220. The bottom oil UV HU 1221 provides a good adhesion base and a preliminary particle touch, and the surface oil UV HU 1220 forms a full and three-dimensional diamond sand particle touch, and presents a sparkling “diamond sand touch” visual effect under light, greatly improving the luxury and technology of the package. The printing ink system forms a hard coating with high cross-linking density after being cured by ultraviolet light, and cooperates with accurate ink amount control, so that the final sand-touching layer has very high surface hardness. The measured GB wear resistance is greater than 1000 times, which is much higher than the conventional matte film or ordinary reverse UV sanding effect, effectively resists scratches and damages in the transportation and handling process, and solves the industry problem of easy scratching and ink dropping of dark packages.
[0050] Further, the ink amount of the bottom oil is 1.5 g / m 2 , which can fully wet the surface of the varnish layer and enhance the adhesion, and also avoids poor leveling or incomplete drying caused by excessive ink amount; the ink amount of the surface oil is 5 g / m 2 , which ensures that the sand-touching particles fully exhibit and are distributed continuously and uniformly. This ratio forms firm bonding between the bottom and surface oils and between the printing ink and the varnish layer, and no peeling occurs after 3 tests of 90-degree reverse folding, significantly improving the folding resistance and interlayer stability.
[0051] In some embodiments, in step S3.1, the pressure of the laminating film is controlled at 160-165 kgf, which can ensure that the PET film is fully attached to the printed substrate, and air bubbles and wrinkles are excluded, and also avoids deformation of the substrate or damage to the ink layer caused by excessive pressure. The good intermolecular bonding significantly improves the stability between the composite layers, preventing problems such as delamination and blistering during subsequent processing. The speed is 20-25 m / min, which ensures efficient and continuous production while ensuring sufficient heat pressing contact time under given temperature and pressure conditions, so that the adhesive layer is fully activated and uniformly transferred, achieving stable and reliable continuous operation, which is suitable for industrial production needs of large quantities of high-end packaging products. The temperature is 95-100°C, which is exactly in the ideal activation temperature range of commonly used hot pressing adhesives such as EVA or PUR pre-coated layers. This temperature can effectively activate the adhesion of the adhesive layer, promote its penetration into the micro-pores of the paper surface and the surface of the PET film, and also prevent the paper from being warped or the ink from being re-stuck due to overheating, ensuring the flatness and dimensional stability of the composite. The daN value after laminating the adhesive should be 36 or higher as tested by the daN pen, which provides an ideal adhesion base for subsequent varnish coating. High surface energy helps the uniform spreading of water-based varnish, avoiding defects such as shrinkage and orange peel.
[0052] In some embodiments, in step S4, the varnish is water-based HH-818. The varnish has excellent wetting and penetration, and can form a uniform and dense coating on the surface of the PET light film. After curing, it significantly improves the surface energy, providing an ideal interface for the firm adhesion of the subsequent sand oil, effectively preventing defects such as peeling and peeling of the sand oil layer during transportation or use.
[0053] The product passes the 4-pound 2-stop 1000-friction test without oil and color loss. The 3M 600 tape test: 3 times at the same position, the shedding area is less than 10% of the tested surface and does not affect reading. The beer folding test, positive and negative respectively pre-folding 180° each 3 times without bubbling phenomenon. After the box test, there is no obvious scratching, bright printing appears. After printing, first paste PET light film on the substrate for protection, after pasting the film, print the sand oil after passing the water-based varnish to enhance the adhesion. The problem of scratching and color loss at the folding position of the packaging box is solved. The effect of platinum positioning photoetching paper is used to realize the effect of main pattern laser silver, which avoids the risk of main pattern wear and sawtooth edge in the printing process.
Claims
1. A high abrasion resistance, scratch resistant, diamond sand pattern making process characterized by: It comprises the following steps: S1, graphic pre-design, according to the required design effect picture, the effect picture has three parts of main pattern, halo and bright light; S2.1, printing ink is printed on platinum positioning paper by UV printing machine to form effect picture; S2.2, the halo and bright light parts of the effect picture which need to be decorated are molded by using holographic lithography technology, so as to produce two effects of lens and laser on the same page; S2.3, the intensity of lens light effect is controlled by printing two groups of special black ink with different color depth in the halo part, and the main pattern part is imaged by laser technology; S3.1, PET light film is pasted, and the product is pasted after printing within 8-12 hours; S3.2, the product pasted with PET light film is put into a constant temperature and humidity workshop for storage for 8-12 hours for processing; S4, the front of the product pasted with PET light film is coated with varnish, and the surface of the product after processing reaches a daoyin value of more than 38; S5, the product coated with varnish is printed with sand feeling oil by UV printing machine, the bottom oil of the sand feeling oil is special sand feeling ink drill diamond oil, and the surface oil of the sand feeling oil is special sand feeling coating drill diamond oil; S6, the product is hit, cut, and formed by sticking box.
2. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 1 wherein: In step S2.1, the printed color order is special black, C, M, Y, and the density of the special black ink, C ink, M ink, and Y ink is 1.2-1.8 g / cm 3 .
3. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 2, wherein: The density of the special black ink is 1.6-1.8 g / cm 3 The density of the C ink is 1.5 g / cm 3 The density of the M ink is 1.4 g / cm 3 The density of the Y ink is 1.2 g / cm 3 .
4. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 1 wherein: In step S5, the model of the special sand feeling ink drill diamond oil is UV HU 1221, and the model of the special sand feeling coating drill diamond oil is UV HU 1220.
5. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 4, wherein: The ink amount of the base oil is 1.5 g / m 2 The ink amount of the surface oil is 5 g / m 2 .
6. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 1 wherein: After step S2.3 and before step S3.1, the adhesion of the ink is tested by 3M tape.
7. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 1 wherein: In step S3.1, the pressure of the pasting film is controlled at 160-165 kgf, the speed is 20-25 m / min, and the temperature is 95-100℃. The daoyin value of the pasted glue is tested by daoyin pen, and the value should reach 36 or more.
8. A high wear resistant, scratch proof, diamond sand pattern making process as claimed in claim 1 wherein: In step S4, the model of the varnish is water-based HH-818.
9. A high wear resistant, scratch proof diamond sand pattern making process as claimed in claim 1 wherein: After step S5 and before step S6, the adhesion of the sand feeling oil is tested by 3M tape, the GB wear resistance test is greater than 1000 times, and the sand feeling oil does not fall off after being folded back 90° three times.